Maternal fitness at the onset of the second trimester of pregnancy: correlates and relationship with infant birth weight. Issue 6 (20th December 2012) - Bisson, M.; Alméras, N.; Plaisance, J.; Rhéaume, C.; Bujold, E.; Tremblay, A.; Marc, I.
Summary What is already known about this subject A healthy life begins in utero and a healthy pregnancy requires a fit and healthy mother. Physical activity during pregnancy provides a stimulation that is essential for promoting optimal body oxygenation and composition as well as metabolic fitness during pregnancy. Although a higher maternal fitness is expected to provide a beneficial fetal environment, it is still unclear whether physical fitness during pregnancy contributes to perinatal health. What this study adds Participation in sports and exercise previously and at the beginning of pregnancy can benefit maternal health by improving cardiorespiratory fitness during pregnancy, irrespective of maternal body mass index. Maternal strength, an indicator of muscular fitness, is an independent determinant of infant fetal growth and can positively influence birth weight. Background It is still unclear whether maternal physical activity and fitness during pregnancy contributes to perinatal health. Objectives The aims of this study were to characterize maternal physical fitness at 16 weeks of pregnancy and to examine its effects on infant birth weight. Methods Maternal anthropometry (body mass index [BMI] and skin‐folds), physical activity, cardiorespiratory fitness (VO2peak) and muscular fitness (handgrip strength) were assessed at 16 weeks of gestation in 65 healthy pregnant women. Offspring birth weight was collected from maternal charts after delivery. Results A higher VO2peak was associated with physical activity spent at sports and exercise before and in early pregnancy (P = 0.0005). Maternal BMI was negatively associated with cardiorespiratory fitness (P < 0.0001) but positively related to muscular strength (P = 0.0001). Unlike maternal cardiorespiratory fitness, handgrip strength was positively associated with infant birth weight (r = 0.34, P = 0.0068) even after adjustment for confounders (adjusted r = 0.27, P = 0.0480). Conclusion A positive relationship between maternal muscular fitness and infant birth weight highlighted maternal strength in pregnancy as a new determinant of infant birth weight.